Analisis Kelas Kuat Papan Laminasi Kombinasi Kayu Sengon dan Bambu Petung: Analysis Of Strength Class of Laminated Board of Combination of Sengon Wood and Petung Bamboo - Wulandari, Febriana; Amin, Radjali (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
Fluctuations in raw wood supply from year to year can be a challenge for wood processing businesses. Sengon wood is one type of fast-growing wood that can be developed by the government as one of the solutions. Sengon wood is a fine to coarse wood with a specific gravity of 0.33 which is included in the light specific gravity range (0.29-0.56) and strength class III-IV. The sengon wood is laminated with bamboo laminate to strengthen the strength of the board. By testing the physical and mechanical properties of laminated boards made from sengon wood and petung bamboo, this study aims to determine whether there is an increase in strength class. The research design used was an experimental factorial design with two components, four treatments, and three replications. Except for the MoE test, all tests evaluating the physical and mechanical characteristics of laminated boards made from sengon wood and petung bamboo were accepted under the JAS 234: 2007. After being converted into laminated boards, the strength class of sengon wood increased from strength class III-IV to strength class III. Sengon wood and petung bamboo can be combined to make laminated boards that can be used for heavy construction.